2020
DOI: 10.1021/acsomega.0c05019
|View full text |Cite
|
Sign up to set email alerts
|

Naphthalene Hydrogenation Saturation over Ni2P/Al2O3 Catalysts Synthesized by Thermal Decomposition of Hypophosphite

Abstract: A series of Ni 2 P/Al 2 O 3 catalysts with different Ni 2 P loadings were synthesized via thermal decomposition of hypophosphite and employed for naphthalene hydrogenation saturation. Results showed that Ni 2 P loading greatly affected Ni 2 P particle size and the number of active sites of the as-synthesized catalysts, which was derived from the variable interaction between POx and Al 2 O 3 . When the hydrogenation saturation reaction was performed at 300 °C, 4 MPa, a H 2 /oil volume ratio of 600, and a liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The isovolumetric impregnation method was employed to synthesize the catalysts as described in our previous work [18], and Ni loading was kept at 10 wt.%. Firstly, a certain amount of nickel acetate tetrahydrate (Ni(CH 3 COO) 2 •4H 2 O, analytical pure, Tianjin Kemiou Chemical Reagent Co., Ltd., Tianjin, China) and ammonium hypophosphite (NH 4 H 2 PO 2 , analytical pure, Aladdin, Shanghai, China) were dissolved in the proper amount of distilled water according to the P/Ni molar ratio of 2 to obtain a uniform solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The isovolumetric impregnation method was employed to synthesize the catalysts as described in our previous work [18], and Ni loading was kept at 10 wt.%. Firstly, a certain amount of nickel acetate tetrahydrate (Ni(CH 3 COO) 2 •4H 2 O, analytical pure, Tianjin Kemiou Chemical Reagent Co., Ltd., Tianjin, China) and ammonium hypophosphite (NH 4 H 2 PO 2 , analytical pure, Aladdin, Shanghai, China) were dissolved in the proper amount of distilled water according to the P/Ni molar ratio of 2 to obtain a uniform solution.…”
Section: Methodsmentioning
confidence: 99%
“…It has been proven that Ni 2 P has the highest catalytic activity among many phosphide catalysts and Ni 2 P catalysts have been applied to aromatic hydrogenation reactions [15][16][17][18][19][20]. Weber et al found that the higher the dispersion of Ni 2 P, the better the hydrodesulfurization performance of the catalyst [21].…”
Section: Introductionmentioning
confidence: 99%
“…The following step was demethoxylation and dehydroxylation to form cyclohexane as a final product. It has been reported that metal phosphide catalysts show remarkably high activity and stability during hydrodesulfurization (HDS), hydrodenitrogenation (HDN), and hydrodearomatization (HDA) of petroleum feedstocks. Oyama and Lee reported a relationship between active sites and the structure of metal phosphide. The crystal structure of Ni 2 P adopts a hexagonal form ( a = b = 0.5859 nm, c = 0.3382 nm), which consists of two types of metal atoms with tetrahedral coordination Ni (1) and square pyramidal coordination Ni (2). , The authors extrapolated the results from the EXAFS characterization with Ni (1) and Ni (2) sites, concluding that they were responsible for different outcomes in HDS.…”
Section: Introductionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) are predominantly present in coal tar, whose direct discharge and insufficient combustion would cause environmental pollution (Hayakawa et al, 2000;Li and Suzuki 2010). Therefore, the treatment of PAHs has gained undivided attention, and hydrogenation of PAHs is an attractive method as it effectively yields the cycloalkanes which can be blended into the jet fuels to improve the volumetric calorific value and combustion performance (Yoon et al, 1996;Zhang et al, 2018;Jing et al, 2020;Jia et al, 2021). However, it is quite difficult to achieve complete saturation while performing the hydrogenation of PAHs with more aromatic rings, and in particular, the saturation of the final aromatic ring is more difficult (Beltramone et al, 2008).…”
Section: Introductionmentioning
confidence: 99%